2021
DOI: 10.1002/wrna.1643
|View full text |Cite
|
Sign up to set email alerts
|

Splicing alterations in healthy aging and disease

Abstract: Alternative RNA splicing is a key step in gene expression that allows generation of numerous messenger RNA transcripts encoding proteins of varied functions from the same gene. It is thus a rich source of proteomic and functional diversity. Alterations in alternative RNA splicing are observed both during healthy aging and in a number of human diseases, several of which display premature aging phenotypes or increased incidence with age. Age‐associated splicing alterations include differential splicing of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 363 publications
(527 reference statements)
1
31
0
Order By: Relevance
“…Diverse splicing defects occur in accelerated aging (progeria) and vascular aging. Changes in the activity of splicing factors and in the production of key splice variants may impact cellular senescence and the aging phenotype [23,65].…”
Section: Pathophysiology Of Mds-how Much Aging?mentioning
confidence: 99%
“…Diverse splicing defects occur in accelerated aging (progeria) and vascular aging. Changes in the activity of splicing factors and in the production of key splice variants may impact cellular senescence and the aging phenotype [23,65].…”
Section: Pathophysiology Of Mds-how Much Aging?mentioning
confidence: 99%
“…Two major risk factors for atherosclerosis are also linked to increased Ptbp1 expression: senescence and integrin-mediated adhesions to fibronectin. Increased Ptbp1 expression has been observed with age and in senescent cells 27,33 . Aging is arguably the single greatest risk factor for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing of RNAs persists across life span, affecting more than a third of genes linked to neural function in human brains [ 7 ]. Mounting evidence has shown that significant changes in alternative splicing occur during aging progression and neurodegenerative diseases [ 11 ]. However, how these splicing changes affect cognition upon progression of aging and age-related neurodegenerative diseases remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that age-dependent RNA binding protein-mediated alternative splicing is responsible for alterations in synaptic structure and function during aging progression. BACE1 , which encodes β-secretase 1 that catalyzes amyloid precursor protein into β-amyloid (Aβ), undergoes extensive alternative splicing upon aging [ 11 , 12 ]. As a result, full-length BACE1 shows an age-dependent increase, resulting in a rise in BACE1 level and a consequent accumulation of Aβ in the brain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%